2009
DOI: 10.3109/01421590902849552
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between findings from the DREEM questionnaire and that from qualitative interviews

Abstract: The DREEM questionnaire can be used qualitatively to assess very specific issues relating to each of the subscales. These findings extend the use of DREEM from quantitative and statistically significant research to qualitative meaning-filled interpretations. The issues then need to be addressed sensitively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 6 publications
5
65
2
Order By: Relevance
“…For all other domain, only one item in each domain showed significant gender difference (SPT-40; SAS -26; SPA -42; SSS -56). Year of study revealed significant differences in 4-items in domains SPT (9,18,29,49 ); one item in SAS (45); 5-items in SPA ( 12,30,35,42,43) and three items in SSS (3,4,46) [Table/ Fig-3].…”
Section: Overall Dreem and Domain Scorementioning
confidence: 99%
See 1 more Smart Citation
“…For all other domain, only one item in each domain showed significant gender difference (SPT-40; SAS -26; SPA -42; SSS -56). Year of study revealed significant differences in 4-items in domains SPT (9,18,29,49 ); one item in SAS (45); 5-items in SPA ( 12,30,35,42,43) and three items in SSS (3,4,46) [Table/ Fig-3].…”
Section: Overall Dreem and Domain Scorementioning
confidence: 99%
“…Several methodologies have been utilized to explore the learning environment like qualitative approaches [5], quantitative [6,7] or both [8,9]. Nevertheless, for most of the health-care related courses [4,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…11 In the process, many of these studies have been able to achieve a number of goals, including the generation of a profile of an institution's/course's strengths and weaknesses, making a comparative analysis within their institution or benchmarking between themselves and another institution and test and apply it as a predictor of student performance. 10 Given the potential usefulness of the DREEM, not only to the institution that utilises it, but to other institutions that can use it as a reference point and the broader international community, it is regretful that the use of such a tool has not been more widespread across Australian health science courses.…”
Section: Introductionmentioning
confidence: 99%
“…Not only do several DREEM items appear in other inventories related to the evaluation of education, 14 but the findings from the DREEM have been found to be consistent with qualitative information attained via interviews. 11 Secondly, even though the DREEM has been used mainly for medical students, it was constructed by a panel of faculty from health profession generally and items were constructed based on their perceptions of learning climates conducive to education in the health professions, not just medicine. 9 Applying the DREEM to a range of Australian health science students would be invaluable on a range of levels.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The Dundee Ready Education Environment (DREEM) inventory is a robust instrument, quantitatively measuring students´perception of the educational environment in relation to different domains, and has proven to have high content and construct validity. 24,25 It has shown consistently high reliability in a diversity of surroundings.…”
Section: Introductionmentioning
confidence: 99%